Assessment of Potential of Sugarcane Bagasse as Substrate in the Growth of Selected Fungal Species - Murjanatu Muhammad Abdullahi; Dauda Abdullahi Machido; Helen I. Inabo (UMYU Journal of Microbiology Research)
The cost of culture media is continuously rising at a very fast rate, thus, there is need to devise means by which low-cost media of comparative performance could be produced. This study was aimed at assessing the potential of sugarcane bagasse (one of the major waste biomasses in Northern Nigeria) to directly support fungal growth, as it contains a considerable amount of nutrients for growth. Isolates of Aspergillus flavus and Trichophyton species obtained from the Department of Microbiology, Ahmadu Bello University, Zaria were used for this study. The sugarcane bagasse was dried, cut into smaller pieces then ground into finer particles (1-2mm diameter) using a milling machine and sterilized in Petridishes by autoclaving. The fungal isolates Aspergillus flavus and Trichophyton species were resuscitated and authenticated using standard procedures, and then inoculated aseptically onto duplicate plates of the sugarcane bagasse and other minerals, and incubated at a temperature of 25oC for 7days. It was observed that the sugarcane bagasse supported a luxuriant and rapid growth of both fungi without any visible form of contamination. It was also observed that A. flavus grew more luxuriantly, consuming about 52.5% of the original amount of the bagasse than Trichophyton species, which consumed 32.5%. Sugarcane bagasse as a growth medium does not essentially meet the needs for growth of every microbe, most especially bacteria, and therefore, it can be used effectively to minimize contamination by microorganisms other than fungi. It can therefore be used as a good alternative and cheaper medium for the detection of fungi in the laboratory. This could also be an easier and cost-effective means by which wastes such as sugarcane bagasse could be removed from the environment, as opposed to using hazardous methods like burning, which could cause air pollution.